Personalized skin health management and nutrition strategies: a comprehensive study based on genetic polymorphisms and dietary factors - Yang, Jitao (Frontiers in Genetics, 2025)
Genetic polymorphism significantly affects an individual’s skin health through various biological pathways such as sensitivity to ultraviolet radiation, antioxidant capacity, inflammatory response, skin barrier function, and natural aging processes. For example, the variation of MC1R gene is associated with red hair and low skin pigmentation, increasing sensitivity to UV radiation, which may accelerate the process of photoaging, such as skin sagging, wrinkles, and pigmentation. Therefore, genetic polymorphism is an important factor in the development of personalized skin health management strategies, which helps to better understand the mechanisms of skin problems and provides theoretical basis for scientific skincare. There is a close relationship between diet, skin health, and skin aging. Many basic and clinical studies have confirmed that diet is the main way for humans to obtain the nutrients needed by the body. Adjusting dietary structure and supplementing specific dietary nutrients can have the effect of delaying skin aging. For example, vitamin C is a powerful water-soluble antioxidant that is crucial for collagen biosynthesis. It can directly promote the expression of collagen genes and eliminate intracellular reactive oxygen species, prevent lipid peroxidation, and delay skin aging. Additionally, SLC23A1 gene encodes antibody transporters, participate in the balance and circulation of vitamin C in the body, and affect the level of vitamin C in the blood. Therefore, in this paper, we integrate multidimensional data including skin genetic testing data, nutrition genetic testing data, dietary and lifestyle questionnaires for data analysis, so that to provide customized nutrition and skincare solutions for each individual. It is expected that combining various omics data and offering personalized solutions will become one of the primary approaches in the field of skin care.